Students readiness in using mathematics online portal: a preliminary study among undergraduates - Chiang, Yan Chiou; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan (Elsevier, 2010)
Numerous teaching and learning methods have been used in this information age especially in distance learning and online learning platforms. Since online portals are mostly designed for online learning, there is a need to investigate students’ readiness in using online portal in traditional universities. This study aims to examine students’ readiness in using Mathematics online portal among undergraduates in Universiti Putra Malaysia. A set of questionnaires, which consists of 22 items, was distributed to 94 respondents. The findings revealed that respondents were satisfied with the facilities provided by the university and responded positively towards the Internet. The respondents are ready to use the online portal based on their technical skills. The findings also showed that students are dissatisfied with Internet connection provided by the university; therefore, the management of the university needs to improve the quality of Internet connection.